Distribution of visuo-attentional resources while reading multiple words - Valentina Bandiera; Lisa S. Arduino; Roberta Daini; Marialuisa Martelli; Silvia Primativo (PLoS ONE, 2026)
Recent studies have investigated the role of semantic processing in the parafovea using the Rapid Parallel Visual Presentation (RPVP) paradigm, which involves the simultaneous presentation of two words, one in the fovea (W1) and one in the parafovea (W2). Results have shown that both accuracy and response times are influenced by the semantic relatedness between the words. These findings suggest that semantic information can be extracted from the parafovea and in parallel with the processing of the foveal word. In the present study, we aimed to provide further evidence of parallel semantic processing and to gain deeper insight into the availability and spatial distribution of attentional resources when semantic relatedness is present. Two experiments were conducted. In both, the first part replicated the previous RPVP setup: two words were simultaneously presented and participants were required to read them aloud. Frequency and semantic relatedness between the two words were manipulated. Results replicated previous findings. Crucially, each experiment included a second task: as participants began reading the two words, a probe (an asterisk) could appear to the right of the parafoveal word (Experiment 1) or above the foveal word (Experiment 2). Probe detection times and accuracy were equally facilitated at both positions when the two words was of high-frequency and semantically related. In contrast, when W1 was of low-frequency, neither accuracy nor reaction times in probe detection benefited from parafoveal processing, suggesting that an increased load on the foveal word hinders parafoveal processing. Finally, the same probe detection results were obtained – both in terms of mean reaction times and accuracy – across the two spatial positions, indicating an even distribution of attentional resources across foveal and parafoveal words.